Credit For Export Bow Penetration: Catalyzing A Breakthrough In The International Trade Sector - Charles, Gerald Ezra; Rangen Jaya, Magnus Hosea (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2023)
International trade, especially through exports, can certainly be an alternative to overcome the various uncertainties that arise due to the Covid-19 pandemic. Unfortunately, in boosting Indonesia's export performance, Indonesia is still faced with the main problem, the narrowness of the export destination market is also a problem that makes Indonesia very dependent on the economic conditions of the main trading partner countries. Credit for Export Penetration is mainly a loan provided to finance export activities to non-traditional markets. Credit for Export Penetration also utilizes collaboration across stakeholders including the Ministry of Trade, Ministry of Industry, trade attache, and ITPC.